Potensi Radar Cuaca dalam Pengamatan Aktivitas Gunung Berapi (Studi Kasus Letusan Gunung Lewotobi Laki-laki 8 November 2024) - Hesti Heningtiyas; Asep Adang Supriyadi; Syachrul Arief (Journal on Education, 2025)
The characteristics of ash volcanoes can be detected using weather radar by analyzing volcanic ash clouds. Weather radar reflectivity data can describe the estimated height of the column of volcanic ash cloud and the trajectory or direction of the eruption cloud. The BMKG's C-band single-polarization weather radar at Maumere Meteorological Station observed several eruptions of Mount Lewotobi Laki-Laki. Mount Lewotobi Laki-Laki is about 60 km from Maumere Weather Radar, which is still included in the radar coverage. From several eruption events, the eruption activity on 8 November 2024 of Mount Lewotobi Laki-Laki could be observed from the Maumere Weather Radar. The radar data processing produces Maximum (MAX) and VCUT (Vertical Cut) products to obtain information on the height of volcanic eruptions and eruption characteristics in more detail. The MAX and VCUT products of weather radar on the eruption event in this study show that the height of the column of volcanic ash cloud observed by weather radar is higher than the direct observation report by PVMBG.